The New Ethnohistory of the Pacific Canadian Region Could Teach Italian Canadians How to Be Worse Settlers and Better Human Beings - Tarsia, Alessandro (Italian Canadiana, 2022)
This article explores the history of the Italian diaspora in British Columbia through the lens of the New Ethnohistory, focusing on the tensions between the perceived continuity of tradition and cultural change. It argues that Italians have actively participated in three different types of colonialism in the Pacific region. First, even though Italian newcomers were almost absent in the early-nineteenth-century “exploitation” era associated with the fur trade and the salmon fisheries, they were later the backbone of the local extractive industries in the second part of the century. Second, the earliest consistent wave of Italians arrived during the “extraction” colonial era (1858–64), associated with gold mining, which also continued in certain areas long afterwards. Third, Italians benefitted from the ongoing structures of “settler colonialism” since the 1860s. This latter type of colonialism is associated with displacing Indigenous peoples and reshaping the landscape through the imposition of European-style agriculture. Indeed, this essay examines some British Columbian case studies of Italian-Indigenous peoples’ interactions as hermeneutical examples that problematize some historiographical tropes. Moreover, it presents the New Ethnohistory, particularly the Community Engaged-Scholarship (CES), as a methodology that could provide Italian Canadians with new historiographical perspectives. Finally, this article invites newcomers to engage in a meaningful reconciliation/conciliation with Indigenous peoples and their flourishing cultures to better comprehend their shared past.